Correction: Multicolour fluorescent carbon nanoparticle probes for live cell imaging and dual palladium and mercury sensors. Issue 36 (5th September 2016) - Sharma, Vinay; Saini, Anoop Kumar; Mobin, Shaikh M.
Abstract : Correction for 'Multicolour fluorescent carbon nanoparticle probes for live cell imaging and dual palladium and mercury sensors' by Vinay Sharma et al., J. Mater. Chem. B, 2016, 4, 2466–2476.